2020
DOI: 10.1111/jcmm.15374
|View full text |Cite
|
Sign up to set email alerts
|

Bone tissue engineering using adipose‐derived stem cells and endothelial cells: Effects of the cell ratio

Abstract: The reconstruction of critical sized bone defects can be challenging in clinical practice. Critical bone defects can be caused by malformation, cancer, trauma or infection. Regardless of the entity, the current gold standard is autologous tissue transfer, which can be associated with significant donor side morbidity and limited tissue availability. One way to circumvent these problems is the generation of bioartificial bone tissue.For bone formation and regeneration, a sufficient vascularization providing oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
3
18
0
Order By: Relevance
“…The unresolved clinical challenges of bone tissue regeneration are related to the limited healing capacity of bone tissue, since current bone tissue regeneration cannot cover all types of bone defects, especially when the bone defect is large and complex. Bone tissue regeneration can be improved if we better understand the exact mechanism that bioactive molecules have on cells involved in bone tissue regeneration [ 61 ]. Moreover, detailed knowledge of the microenvironment at the defect site and how this affects and interacts with cells in the engineered bone is needed.…”
Section: Osteocytes Governing Bone Regenerationmentioning
confidence: 99%
“…The unresolved clinical challenges of bone tissue regeneration are related to the limited healing capacity of bone tissue, since current bone tissue regeneration cannot cover all types of bone defects, especially when the bone defect is large and complex. Bone tissue regeneration can be improved if we better understand the exact mechanism that bioactive molecules have on cells involved in bone tissue regeneration [ 61 ]. Moreover, detailed knowledge of the microenvironment at the defect site and how this affects and interacts with cells in the engineered bone is needed.…”
Section: Osteocytes Governing Bone Regenerationmentioning
confidence: 99%
“…In this regard, heterotypic cell contacts between endothelial cells and osteoprogenitor cells seem to be the driving force [19]. In a recent work we demonstrated that coculturing adipose derived stem cells (ADSCs) and human umbilical vein endothelial cells (HUVECs) stimulates proliferation, proangiogenic effects and osteogenic differentiation [13]. We translated our in vitro results into the rat arteriovenous loop (AV loop) model.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the application of VEGFA165 reduced the cell number of HUVECs under monoculture conditions compared to the control group. Based on the findings from a previous study, it is alluring to speculate that VEGFA165 concentrations higher than 200 pg/mL might have adverse effects on HUVEC proliferation [13]. From the pertinent literature, it is well-known that VEGF can stimulate the proliferation rate of ADSCs in a dose dependent manner [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations